Reconstruction of Marriage Dispensation Regulation in the Ethic Perspective of Care - Yayat Dimyati (Al-Mawaddah: Jurnal Studi Islam dan Hukum Keluarga (Ahwal Al-Syakhsiyyah), 2025)
This study aims to reconstruct the regulation of marriage dispensation in Indonesia through the perspective of Ethic of Care which emphasizes the value of care, empathy, and moral relationships in legal decision-making. The marriage dispensation regulation contained in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 and Supreme Court Regulation (Perma) Number 5 of 2019, basically seeks to protect children from the practice of early marriage. However, in practice, many dispensation decisions are still oriented towards legal formalism and socio-economic considerations alone, not in the best interest of the child. Through the Ethic of Care approach, this research offers a new paradigm that places affective, relational, and moral aspects as the basis for consideration by judges and policymakers in determining the marriage dispensation. This approach is expected to strengthen child protection while building a more humanistic and contextual legal policy. Thus, this study concludes that the Ethic of Care can be a new ethical and philosophical foundation for family law reform in Indonesia, especially in the context of marriage dispensation. This paradigm places law not just as a system of state orders, but as a means of maintaining life (caring justice). Care-based reconstruction will strengthen the protective function of the law against girls, who have often been victims of early marriage practices due to cultural or social pressures. Finally, the implementation of Ethic of Care in the regulation of marriage dispensation is expected to be able to give birth to a family law system that is more substantive justice, responsive to human values, and morally civilized. This paradigm not only corrects the weaknesses of legal formalism, but also restores the function of law as an instrument that hears, understands, and cares for human lifeso that every legal decision is not only juridically valid, but also ethically and humanly correct.